Assessment of Fish Health Status Under Long-Term Water Pollution : Vygozero Reservoir , North-West Russia - Belicheva, Lidia A.; Sharova, Julia N. (Environment. Technology. Resources. Proceedings of the International Scientific and Practical Conference, 2015)
Environmental pollution and its effects on the health of aquatic ecosystems is a great problem that has been studied intensely in the last years. The Vygozero reservoir is one of the largest water bodies of the Karelian Republic. Its ecosystem has undergone significant changes since the 1930s mainly due to anthropogenic influence from the development of pulp and paper mill industry leading to accumulation of toxic contaminants and eutrophication. At present, the water body has been shown to be also polluted by hydrocarbon products and heavy metals. Among the huge changes in Vygozero ecosystem is the decrease of some fish populations and partial loose of commercial fishing importance. Despite the obvious changes in fish population the chronic biological effects of the Vygozero reservoir pollution on fish organism are poorly studied. This study is concerned with the evaluation of pollution influence on fish health status and establishment relation between fish health and environmental quality. The parameters selected for this aim were the occurrence of gills, liver and kidney alterations, as histopathological changes are widely used as biomarkers in the evaluation of the health of fish exposed to contaminants. Our findings confirm chronic pollution of the Vygozero reservoir. Histological analysis of fish tissues revealed a variety of progressive, regressive, inflammatory, circulatory disturbances and neoplastic changes. Observed histological alterations indicate that organism of fish from Vygozero reservoir responses to the impaired environment quality. Revealed histopathologies are sings of metabolic disorders, immunity suppression, compensatory reactions development and functional abnormalities in vital organs of studied fish. The results of the study correspond to the prior research devoted to ascertain tissue changes in different fish species taken from an area with chronic multiple anthropogenic impact. So it can be concluded that histopathological lesions are result of long-term effect of toxic xenobiotics.